2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--19949
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Flipped First-Year Engineering Course

Abstract: has worked in four distinct areas: waste management operations research, contaminated site assessment and remediation, education innovation, and sustainable engineering. He has employed a wide variety of techniques, including computer modeling, laboratory experiments, field testing, and surveys. His current research focuses on energy conservation, alternative energy generation, engineering learning communities, and hybrid courses (courses with classroom and on-line aspects).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Regarding students' perceptions/ opinions or views about flipped classrooms, the review displayed similar results since the previous studies reported that learning environment was taught to be more flexible (Kiat & Kwot, 2014;Mok, 2014;Simpson, Evans, Eley, & Stiles, 2003), it fosters peer interaction and cooperation (Bailey & Smith, 2013;Love et al, 2014;Talbert & Valley, 2012), students come to class prepared ( Mok, 2014), they preferred flipped classroom over traditional methods (Butt, 2014;Gilboy, Heinerichs & Pazzaglia, 2015;Love et al, 2014;Roach, 2014), they developed a better comprehension of the content (Simpson & Richards, 2015). In terms of the disadvantages and limitations, studies reported that students found the lecture videos boring and long (Amresh, Carberry & Femiani, 2013;Olson, 2014;Ossman& Warren, 2014), they experienced technical problems related to the computers and internet connection (Everett, Morgan, Stanzione& Mallouk, 2014;Tague & Baker, 2014), and they had problems due to their lack of readiness and unfamiliarity to the method (Amresh et al, 2013;Bland, 2006;Margoniner, 2014;Talbert & Valley, 2012).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Regarding students' perceptions/ opinions or views about flipped classrooms, the review displayed similar results since the previous studies reported that learning environment was taught to be more flexible (Kiat & Kwot, 2014;Mok, 2014;Simpson, Evans, Eley, & Stiles, 2003), it fosters peer interaction and cooperation (Bailey & Smith, 2013;Love et al, 2014;Talbert & Valley, 2012), students come to class prepared ( Mok, 2014), they preferred flipped classroom over traditional methods (Butt, 2014;Gilboy, Heinerichs & Pazzaglia, 2015;Love et al, 2014;Roach, 2014), they developed a better comprehension of the content (Simpson & Richards, 2015). In terms of the disadvantages and limitations, studies reported that students found the lecture videos boring and long (Amresh, Carberry & Femiani, 2013;Olson, 2014;Ossman& Warren, 2014), they experienced technical problems related to the computers and internet connection (Everett, Morgan, Stanzione& Mallouk, 2014;Tague & Baker, 2014), and they had problems due to their lack of readiness and unfamiliarity to the method (Amresh et al, 2013;Bland, 2006;Margoniner, 2014;Talbert & Valley, 2012).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…However, if videos that were produced for the selfstudy phase can be used again in subsequent years, the time required for preparation on the part of the teachers and lecturers is considerably reduced. Learners often complain about technical problems, such as internet connection speeds (Everett et al, 2014). Observations have shown that technical problems often occur due to a lack of equipment or non-functioning school servers (Werner et al, 2018).…”
Section: Research Resultsmentioning
confidence: 99%
“…Learners can perform better (see Table 3) Learners can learn at their own pace (e.g. watch videos several times) (Nouri, 2016) Learners work on cognitively more demanding tasks while being supervised (Lee & Lai, 2017) Teachers are more flexible in class (Bergmann & Sams, 2014) Mostly positive perception of the FC by learners (Bishop & Verleger, 2013) Video material can be used several times Success of the method depends heavily on learner's preparation during the self-study phase (Karanicolas et al, 2016) Mandatory internet connection and playback media (Clemens et al 2013;Everett et al, 2014) Learners are often overwhelmed with new approaches (Amresh et al 2013;Bland, 2016) Learners have problems organizing themselves within the FC (Margoniner, 2014) Increased workload, especially on forehand (Ghadiri et al, 2014;Kalavally et al, 2014) Insights gained from research into the FC approach make it clear that a theoretical framework for a uniform design and implementation is still lacking. The basic form of the Flipped Classroom, based on Finkenberg (2018), offers one possibility for unifying the design.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…Self-paced learning allows students to control the learning schedule that suit their needs and learning goals. [7,8] This control also allows students to revisit the material as many times as they need aiding learning for those students who might be averse to asking questions of their instructors about the same topic again and again. The feedback collected in the study presented shows that students really liked the ability of choosing their own pace and being prepared for the class ahead of time.…”
Section: Proceedings Of the 2018 Asee Midwest Section Annual Conferencementioning
confidence: 99%